2015
DOI: 10.1038/nrurol.2015.276
|View full text |Cite
|
Sign up to set email alerts
|

An update on the diagnosis and management of ejaculatory duct obstruction

Abstract: Ejaculatory duct obstruction (EDO) remains a rare but surgically correctable cause of male sexual dysfunction and male infertility due to obstructive azoospermia, diagnosed in up to 5% of infertile men. EDO should, therefore, be considered within the list of differential diagnoses for men undergoing infertility investigations, with work up including clinical examination, transurethral ultrasonography, semen analysis, chromotubation, seminal vesiculography and seminal vesicle aspiration. Obstruction can be limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…Furthermore, Yang et al () observed that in most cases, obstruction was present at the level of the seminal colliculus. Modgil et al () reported that obstruction was limited to the distal ends of the ejaculatory ducts. The region within the seminal vesicle system prone to calcification or obstruction corresponds to the second or third segment described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yang et al () observed that in most cases, obstruction was present at the level of the seminal colliculus. Modgil et al () reported that obstruction was limited to the distal ends of the ejaculatory ducts. The region within the seminal vesicle system prone to calcification or obstruction corresponds to the second or third segment described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the calcineurin pathway also plays pivotal roles in plant and animal fungal pathogens (25,26). In C. neoformans, which causes fatal systemic cryptococcosis and meningoencephalitis (27), the calcineurin pathway is required for maintenance of cell wall integrity and survival at mammalian body temperature (28). In C. albicans, which causes both superficial and systemic candidiasis (29), calcineurin is required for survival in the presence of serum (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…Although vasography is accepted as the gold standard for diagnosis, transrectal ultrasound (TRUS) has become the essential imaging modality because of its less invasive nature (6). The standard treatment procedure for distal EDO is transurethral resection of the ejaculatory ducts (TURED) (7).…”
Section: Introductionmentioning
confidence: 99%